Model of innovation in agriculture 4.0 processes in the department of Cundinamarca, Colombia - Carlos Alberto Almanza Junco; Yenny Katherine Parra Acosta; Mauricio Sabogal Salamanca (Tendencias, 2024)
Innovation in agriculture plays a fundamental role in the transition of said production towards more sustainable schemes, hence the importance of its study, especially in relation to production processes. The literature shows that although several studies have been carried out that examine the variables that intervene in the innovation processes in the agricultural sector, there is a lack of studies that examine the innovation processes in Colombia. This is why the fundamental objective of this research is to develop a model that explains the main factors that are related to process innovation in the agricultural sector, using concepts derived from organizational innovation process models developed in the literature. The factors identification methodology used a sample of 1,190 Agricultural Production Units (UPA) collected in the National Agricultural Survey, incorporating only producers from the department of Cundinamarca, Colombia. With this sample, and using for the analysis the variables that are developed in the literature, a principal components factorial analysis was carried out, as well as a second-order confirmatory factorial analysis. The factor analysis shows three latent factors, among them “Innovation in Raw Materials”, “Innovation in crops” and “Innovation in management of External Factors”, which, being the most significant for the process innovation process, should be considered as fundamental part of the government's public policies to facilitate its adoption in Colombian agriculture in the future.